THE TREND IN MANAGEMENT – DIGITAL MANAGEMENT AND HOW IT IS IMPLEMENTED BY NATIONAL AND INTERNATIONAL SMES - BORCOȘI CORINA ANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The management represents the art of creating, maintaining and developing: businesses, managers, employees and their work. The trend in management will follow the trend of today's life, which is lived in an increasingly digitalized environment. Our professional and personal development, work activity is increasingly influenced by digital technologies. Digitalization, the implementation of digital technologies will require employees who have more and more skills in the digital field and who are increasingly better trained. Thus, school will be increasingly important. It was mistakenly believed that with the introduction of technologies (today we are talking mainly about the use of digital technologies), they will replace human work, which did not happen in reality. All technologies are just tools for employees to become more efficient, the business to be more profitable, employees to be increasingly trained, and their work to become easier to do and in a shorter time. There is a great interest in integrated of all technologies, because these are real tools to obtain as many advantages as possible in as little time as possible and use as fewer resources as possible. We have fast internet connections, increasingly powerful computers; cloud computing, artificial intelligence, these being among the most important digital tools, which can be capitalized on in today's digital era. Management is a living organism, which, living in today's times, adapts to the current increasingly digitalized environment. Thus, it tends to digitize itself more and more in its activity by using digital tools such as: artificial intelligence, cloud computing, the internet, the computer, for forecasting activities, for developing strategies, for planning activities, for human resources management, for planning production, for risk management, etc. The paper presents the current characteristics of the digital environment, in which we live, but also what are the characteristics of digital management. SMEs and their importance for the economy and society are also presented, along with the ways of implementing digital management by Romanian SMEs and by SMEs at an international level. The paper ends with conclusions and proposed research topics for the future, inspired by the theme presented in this paper.